Targeting Oxidative Stress With Auranofin or Prima-1Met to Circumvent p53 or Bax/Bak Deficiency in Myeloma Cells - Tessoulin, Benoit; Descamps, Geraldine; Dousset, Christelle; Amiot, Martine; Pellat-Deceunynck, Catherine (Frontiers in Oncology, 2019)
Prima-1Met (APR-246) was previously shown to be dependent on glutathione inhibition and on ROS induction in cancer cells with mutated or deleted TP53. Because this ROS induction was, at least in part, due to a direct interference with the thioredoxin reductase enzyme, we investigated whether activity of Prima-1Met could be mimicked by auranofin, an inhibitor of the thioredoxin reductase. We thus compared the activity of auranofin and Prima-1Met in 18 myeloma cell lines and in 10 samples from patients with multiple myeloma or plasma cell leukemia. We showed that, similar to Prima-1Met, the activity of auranofin was not dependent on either TP53 status or p53 expression; was inhibited by N-acetyl-L-cysteine, a ROS scavenger; displayed a dramatic synergy with L-buthionine sulfoximine, an irreversible inhibitor of glutathione synthesis; and induced cell death that was not dependent on Bax/Bak expression. These data showed that auranofin and Prima-1Met similarly overcome cell death resistance in myeloma cells due to either p53 deficiency or to mitochondrial dysfunction.